2018
DOI: 10.3126/jmrd.v3i1.18926
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of locally developed black light trap for maize insects monitoring in Chitwan, Nepal

Abstract: Till today, the light traps in Nepal are found using with traditional type, which have not being recognized internationally. These light traps were of low efficiency for trapping insects as compared to black light trap (BLT). The black light tube (F10T8/BL) was used in newly constructed trap at National Maize Research Program (NMRP), Rampur, Chitwan, Nepal. Both traps were installed at the maize experimental field at NMRP during February to October, 2017. Data on insect numbers were recorded once in a week fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The present finding indicates that late sowing performed better in regards to infestation by maize stem borer than early sowing. The present finding in agreement with Bhandari et al (2018) who reported that effect of planting dates of maize on the incidence of borer. The data on the three dates of sowing showed that the maize sowed on 5 th April suffered the least maize infestation followed by maize sowed on 21 st March, in contrast with the maize sowed on 6 th March, which recorded the highest infestation.…”
Section: Infestation At 60 Dassupporting
confidence: 94%
“…The present finding indicates that late sowing performed better in regards to infestation by maize stem borer than early sowing. The present finding in agreement with Bhandari et al (2018) who reported that effect of planting dates of maize on the incidence of borer. The data on the three dates of sowing showed that the maize sowed on 5 th April suffered the least maize infestation followed by maize sowed on 21 st March, in contrast with the maize sowed on 6 th March, which recorded the highest infestation.…”
Section: Infestation At 60 Dassupporting
confidence: 94%
“…Farmers must know that by attracting and killing one adult moth or insect they control around 300-400 insect progenies through them. By monitoring the light traps, they will know better what types of insects are there in the field and whether they are in controllable level or not [7][8][9][10]. The light trap has undergone lots of changes from its simple beginning as a kerosene lamp kept in front of a cloth sheet or water container to electrically operated ones to battery operated now [11,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury-vapour lamps attract more species and individuals of moths than the UV light alone probably since they have high peaks both in the UV and in the visible spectrum (Jonason et al 2014;Tikoca et al 2016;Brehm 2017). In case of Lepidoptera blacklight (BL) tube (Belton and Kempster 1963;Mészáros 1966;Bhandari et al 2017) and LED lights with wide spectra including UV radiation (Brehm 2017;Infusino et al 2017) can be also effective. For attracting mosquitos, the incandescent lights, for agricultural pests the green lights, and for some aquatic insects the cyalume lightsticks are the most commonly used light sources (Epsky et al 2008).…”
Section: Introductionmentioning
confidence: 99%